What’s right (leaning) with Kansas media: the cultivation of misinformation in rural America - Vogts, Todd R. (Kansas State University, 2023)
Misinformation and disinformation have shown the potential to fertilize distrust in the news (Kalogeropoulos et al., 2019; Karlsen & Aalberg, 2021; Swart & Broersma, 2022), which can allow democracy-damaging polarization to grow within the United States. This polarization often takes root due to the erosion of reliable information that can be exacerbated by confirmation bias that may cultivate filter bubbles and echo chambers (Flaxman et al., 2016; Lee et al., 2021; Nechushtai & Lewis, 2019; Pearson & Knobloch-Westerwick, 2019). In many cases, politically motivated individuals and media outlets plant these seeds of misinformation and disinformation intentionally, leaving members of society to graze on the subsequent silage of content. If it lacks nutrients, this information constructs a skewed perception of society. This weakens the social capital bonds that germinate a functioning democracy, which sprouts from reliable and public knowledge (Belair-Gagnon et al., 2019; Lewis et al., 2014; Putnam, 2001). In order to prune misinformation and disinformation from the fields of democracy that are irrigated by journalism’s flow of truth, the pathways to news that individuals take and lead them to the invasive species of information must be considered. This risk is particularly important as it relates to the news consumption habits of rural Americans, who largely live and work in agrarian communities and exist as an important voting block as was evident in the 2016 election of President Donald Trump and the controversy surrounding the outcome of the 2020 election. However, most current research does not examine this group in specific focus or simply largely ignores this swath of the United States population as just “fly-over” country. Thus, with the purpose of filling a crucial gap in the literature, this study investigated the pathways to news for individuals living and working in rural areas of the country, specifically rural Kansas. As the investigative focal point, rural Kansas provides a vital case study to explore how rural citizens come to believe in, and potentially further spread misinformation and disinformation, including conspiracy theories spread by partisan media outlets that include, but are not limited to, talk radio, cable television, and social media. Through the implementation of interviews and an online survey that collected data from these individuals, this dissertation reports how individuals in rural Kansas access and use news in ways that stimulate political division and set the stage for polarization to flourish (Bail et al., 2018; Darr et al., 2021; Gaultney et al., 2022; Talisse, 2021), which can lead to a bruised and battered democracy. This method of inquiry sprouts from the social constructionism perspective of reality. This dissertation thereby positions the media effects theories of Cultivation Theory (CT), Uses and Gratifications Theory (U&G), and Communication Infrastructure Theory (CIT) as the optimal lenses through which to examine the pervasive problem of misinformation and disinformation by seeking the root cause of this noxious information’s spread. To that end, this study found that social media and news websites, television, and radio are the primary pathways to news for rural Kansans. The bulk of the content being consumed via these media comes from national and partisan sources, and, in many cases, it consists of opinion-based material. Driven by the state’s strong religious alignment (Wuthnow, 2012) and predominantly conservative political stance (Kansas Secretary of State, 2023), the media messages align with the previously held beliefs of the residents, even if the information is inaccurate. This leads to those beliefs becoming more entrenched, and the misinformation and disinformation spreads when individuals discuss the news with their peers. The fact that individuals do not recognize inaccurate or false information for what it is indicates a deficiency in terms of media literacy skills. Such a finding was made even more evident by several participants expressing their deeply held beliefs in various conspiracy theories. Compounding this issue is the pervasive lack of trust in the media reported by the respondents. In most cases, individuals said they have little to no trust that they are receiving accurate and complete information from news outlets. This was particularly true in terms of national outlets, and although confidence still wasn’t high, local news was found to be more trustworthy. Still, the overall results suggested that rural Kansans desire more reliable news and information, especially at the local level. Individuals indicated they believed journalism was important for society, and this was even more true locally because study participants suggested engaging socially and politically at that level proved to be more impactful than at the national level. Therefore, the implications of this study are multifaceted. First, misinformation and disinformation are being cultivated in rural Kansas because of the residents’ media consumption homogeneity. Also, media literacy skills need to be improved, which can be achieved through educational initiatives. Furthermore, rural Kansans need to be given better news options, and a primary way to achieve this is to improve local news and access to local news across modalities.
Keywords: Rural Kansas; Pathways to news; Trusting the news; Community media; Misinformation; Disinformation